Akurasi Nilai Peramalan Harga Cabai Rawit Merah di Kota Makassar dengan Metode Single Exponential Smoothing - Arisandi, Arwini (Program Studi Matematika Universitas Sulawesi Barat, 2025)
Red cayenne pepper is a food commodity that is widely cultivated in Indonesia. This chili is in demand from domestic to foreign markets, so the price of chili can fluctuate under certain conditions. This is a concern that forecasting chili prices is important as a step for policymakers in making policies. Data obtained from the Makassar City Food Security Service amounted to 671 data (days) modeled using the single exponential smoothing forecasting method, which aims to assess the ability of forecasting results for the price of red cayenne pepper in Makassar City. The results show that descriptively the lowest chili price occurred in September 2023 at IDR 13,000 to IDR 15,000, while the highest chili prices will occur at the end of 2023 at IDR 70,000 to IDR 80,000. The resulting MAPE value is 6.50% < 10%, so it is concluded that the single exponential smoothing model provides excellent forecasting capabilities in forecasting the price of red cayenne pepper in Makassar City.